Manajamen Pembelajaran Luring dan Daring (Synchronous dan Asynchronous) pada Masa Pandemi Covid 19 Di MTs.N 5 Lombok Tengah Tahun Pelajaran 2021/2022 - Abdul Hannan (Universitas Hamzanwadi, 2022)
The education field is severely afflicted by the tense atmosphere caused by the Covid-19 outbreak. Numerous schools are closed and scarcely open to conduct short face-to-face (FTF) meetings. This results in a less effective learning process that impacts the education quality. For this reason, several schools are completely closed during the pandemic. Meanwhile, some schools reduce the provisions of FTF classes and implement health protocols by carrying out the instruction virtually. State Islamic Junior High School (MTsN) 5 Central Lombok is one of the Islamic schools that runs offline and online learning processes. Thus, this qualitative research intends to interpret phenomena that occur in various ways involving abundant existing methods. Hence, the findings indicated that the implementation of learning at MTsN 5 Central Lombok employs the Blended learning system. The performance of offline and online learning is the principal's policy based on the meeting results between the school and the school committee—applying the learning process with shifts. The implementing technique of offline learning evaluation is left to each teacher to deliver materials virtually. In addition, the evaluation of e-learning via WhatsApp and Zoom platforms tightens health protocols during FTF learning. Synchronous and asynchronous online implementations require adequate planning. Principals continuously monitored e-learning performance. However, the learning process via Zoom meetings is hindered by several problems, including not all students having a Smartphone, a lack of signal, and the need for a lot of balance or internet quota.